3D active dynamic actuation model for offshore cranes. (27th March 2021) - Fantuzzi, Nicholas; Rustico, Althea; Formenti, Massimiliano; Ferreira, Antonio J. M.
Abstract: The handling of offshore payloads is a critical operation that presents numerous challenges, in particular related to the required precision in controlling their oscillations in a safe and accurate manner. The uncontrolled payload oscillations induced by the rolling movement of the vessel have been historically mitigated by the experience of on‐deck operators by means of taglines. The availability of experienced personnel is not always present, and a manual control operation still presents inconsistent performances and a high risk for the safety of men and machines. This study presents a novel approach to an antisway control conceived to mitigate such problems and possibly to automate some of the operations concerning the payload sway control that are currently done manually. In particular, a system consisting of a translating trolley actuated through a proportional–integral–derivative controller is taken into consideration to mitigate the oscillations induced by the vessel's rolling and pitching motion onto a three‐dimensional 8 degrees of freedom with double‐pendulum model representing the hanging payload. The study is completed through an analysis aimed to characterize the bandwidth and frequency response of the controlled closed‐loop system and highlight all the potential areas of interest for which further characterization is needed.